Media Sosial Sebagai Pemasaran Digital untuk Perajin Kain Songket di Desa Penyandingan - Desiani, Anita; Gofar, Nuni; Andriani, Yuli; Irmeilyana, Irmeilyana; Nabila, Annisa; Muzayyadah, Fathona Nur; Syarifuddin, Fauzi Yusuf; Kurnia, M Kahfi Aldi (Universitas Nusantara PGRI Kediri, 2022)
Penyandingan Village is part of the Ogan Ilir District, Indralaya District. Songket craftsmen are the main source of income besides farmers and traders in the Penyandingan village. Nearly 90% of the women in the Penyandingan village are songket craftsmen. The difficulty of songket craftsmen is in terms of marketing their handicrafts. Craftsmen need breakthroughs so that their products are widely distributed, one of which is utilizing information technology such as social media. Many economic actors, both individuals and groups, use social media to market their products. Unfortunately, the knowledge of pairing village songket craftsmen is still lacking in utilizing social media in marketing songket fabrics such as promotions on Instagram, business WhatsApp, and business Facebook. By implementing the use of social media in the marketing of songket cloths from Penyandingan village, it can help increase village income and promoting the songket cloth of Penyandingan village.